2022
DOI: 10.1186/s12985-022-01784-4
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV2 RT-PCR assays: In vitro comparison of 4 WHO approved protocols on clinical specimens and its implications for real laboratory practice through variant emergence

Abstract: Introduction RT-PCR testing on nasopharyngeal swabs is a key component in the COVID-19 fighting, provided to use sensitive and specific SARS-CoV2 genome targets. In this study, we aimed to evaluate and to compare 4 widely used WHO approved RT-PCR protocols on real clinical specimens, to decrypt the reasons of the diverging results and to propose recommendations for the choice of the genome targets. Methods 260 nasopharyngeal samples were randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In this regard, we observed a discrepancy between CDC and Berlin positive results (59% and 34%, respectively) using RNA extracted from saliva samples ( Table 1 ). According to a previous study, four WHO approved RT-PCR diagnostic protocols for SARS-CoV-2 (including those used in our study) showed discordant results in almost 30% of cases evaluated [ 74 ]. Additionally, Berlin RdRp-SARSr primers-probe set has been reported to show low sensitivity compared with other primers-probe sets [ 75 ].…”
Section: Discussionmentioning
confidence: 77%
“…In this regard, we observed a discrepancy between CDC and Berlin positive results (59% and 34%, respectively) using RNA extracted from saliva samples ( Table 1 ). According to a previous study, four WHO approved RT-PCR diagnostic protocols for SARS-CoV-2 (including those used in our study) showed discordant results in almost 30% of cases evaluated [ 74 ]. Additionally, Berlin RdRp-SARSr primers-probe set has been reported to show low sensitivity compared with other primers-probe sets [ 75 ].…”
Section: Discussionmentioning
confidence: 77%
“…It has to be kept in mind that there is considerable variability in Ct values of a given concentration when using different primers and probes and the IP4 assay used here gives relatively high Ct values compared to some other techniques. 43 The most diluted solution (Figure 4a) has in our case a Ct The sensor was tested in addition for its selectivity in discriminating between SARS-CoV-2…”
Section: Sensors and Diagnostics Accepted Manuscriptmentioning
confidence: 99%
“…Overall, ORF1ab was more likely to go undetected, leading to discrepancies in the results of 2 targets of the same assay ( Table 1 ). Similarly, Gdoura et al reported that 94.9% of the discrepancy in the results of the DaAn assay were caused by a single positive amplification of the N when detecting the Alpha variant [23] . On the contrary, Wang et al identified more mutations to the targets of probes and/or primers based on the N versus the E and RdRp sequences of the ORF1ab fragment [24] .…”
Section: Discussionmentioning
confidence: 95%